Immune Response on Optimal Timing and Fractionation Dose for Hypofractionated Radiotherapy in Non–Small-Cell Lung Cancer - Zhao, Xianlan; Li, Jixi; Zheng, Linpeng; Yang, Qiao; Chen, Xu; Chen, Xiewan; Yu, Yongxin; Li, Feng; Cui, Jianxiong; Sun, Jianguo (Frontiers in Molecular Biosciences, 2022)
Background: The intervention timing of immune checkpoint inhibitors (ICIs) and radiotherapy fractionations are critical factors in clinical efficacy. This study aims to explore dynamic changes of the tumor immune microenvironment (TIME) after hypofractionated radiotherapy (HFRT) at different timepoints and fractionation doses in non–small-cell lung cancer (NSCLC). Methods: In the implanted mouse model, the experimental groups received HFRT 3.7 Gy × 4 F, 4.6 Gy × 3 F, 6.2 Gy × 2 F, and 10 Gy × 1 F, respectively, with the same biological equivalent dose (BED) of 20Gy. Tumor volume and survival time were compared with those of the control group. Flow cytometry was performed to detect immune cells and their PD-1/PD-L1 expressions using tail-tip blood at different timepoints and tumor tissues at 48 h after radiotherapy. In NSCLC patients, immune cells, PD-1/PD-L1, and cytokines were detected in peripheral blood for 4 consecutive days after different fractionation radiotherapy with the same BED of 40Gy. Results: Tumor volumes were significantly reduced in all experimental groups compared with the control group, and the survival time in 6.2 Gy × 2 F (p < 0.05) was significantly prolonged. In tail-tip blood of mice, CD8+ T counts increased from 48 h to 3 weeks in 4.6 Gy × 3 F and 6.2 Gy × 2 F, and CD8+ PD-1 shortly increased from 48 h to 2 weeks in 6.2 Gy × 2 F and 10 Gy × 1 F (p < 0.05). Dentritic cells (DCs) were recruited from 2 to 3 weeks (p < 0.01). As for NSCLC patients, CD8+ T counts and PD-1 expression increased from 24 h in 6.2 Gy × 4 F, and CD8+ T counts increased at 96 h in 10 Gy × 2 F (p < 0.05) in peripheral blood. DC cells were tentatively recruited at 48 h and enhanced PD-L1 expression from 24 h in both 6.2 Gy × 4 F and 10 Gy × 2 F (p < 0.05). Besides, serum IL-10 increased from 24 h in 6.2 Gy × 4 F (p < 0.05). Conversely, serum IL-4 decreased at 24 and 96 h in 10 Gy × 2 F (p < 0.05). Conclusion: HFRT induces the increase in CD8+ T cells and positive immune cytokine response in specific periods and fractionation doses. It was the optimal time window from 48 h to 2 weeks for the immune response, especially in 6.2 Gy fractionation. The best immune response was 96 h later in 10 Gy fractionation, delivering twice instead of a single dose. During this time window, the intervention of immunotherapy may achieve a better effect.